Hubungan menopause dengan depresi pada wanita diatas 50 tahun - Carla Octavani; Meiyanti Meiyanti (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: Depression is a significant contributor to the global burden of disease and affects people in all communities across the world. Today, depression is estimated to affect 350 million people with apercentage of 50% higher for females than males. Several theories have been proposed to explain this phenomenon which includes biological, psychological, and social factors. Some researchers conclude the prevalence of depression is quite high in women, especially when a woman reaches her menopause period.Objective: This study aims to know the relationship between menopause and depression among female above 50 years old.Methods: An analytical observational study with a cross-sectional design was carried out from August to October 2016. The samples were selected using non-probability sampling, consecutive sampling method of 108 subjects. Data were collected using a questionnaire which included the characteristics of the subject (age, education, occupation, menopausal state) and the Beck Depression Inventory to measure the level of depression. Chi-Square test and Fisher test were used to analyse data with the significance test at p< 0.05.Results: A total of 56 (51.9%) subjects aged 50-60 years and as many as 85 subjects (78.7%) experienced menopause. The prevalence of menopause and depression among women above 50 years old is 20%. The statistical analysis showed there was no significant correlation between two variables (p=1).Conclusion: There is no correlation between menopause and depression among women above 50 years old.